Critique of Capitalist Ideology in Bhattarai’s Muglan - Lamichhane, Hari Krishna (Literary Studies, 2021)
This article explores Govinda Raj Bhattarai’s worries about the innocent youths to be the Muglanis forced by the dominant capitalistideology of the society in his novel Muglan. In the novel, he presents the critical situation of the youths who are compelled to leave their motherland just for survival but they get sold like cattle and are enslaved and forced to do hard physical labour in the cruel foreign land. The article applies neo-Marxist insights to study devastating results of elitist bourgeois ideology of the society over the life of poor innocent people in the novel. It mainly borrows ideas from Luis Althusser’s “Ideology and Ideological State Apparatuses” along with the ideas by Terry Eagleton and Antonio Gramsci. The article shows Bhattarai’s critique of elitist bourgeois ideology of the society that he does through his choice of the protagonist, Sutar, who along with other youths leaves his home and goes to muglan but gets robbed, sold and forced to work as road builder in the foreign land of Bhutan. By showing the hopelessness of better life for the youths in their native land, Nepal and their pathetic condition in the foreign land, Bhattarai critiques the elitist ideology of Nepalese society.